IM transition sets - Stott, M. J. (Swimming World Magazine, 2019)
Ken Heis, head coach of the Mason (Ohio) Manta Rays, has a studied approach to IM training, honed by experimentation and experience. Here the four-time Ohio Swimming Coach of the Year shares some sample IM transition sets.